Anodized Aluminum Oxide Templated Synthesis of Metal–Organic Frameworks Used as Membrane Reactors. (5th December 2016) - Yu, Yifu; Wu, Xue‐Jun; Zhao, Meiting; Ma, Qinglang; Chen, Junze; Chen, Bo; Sindoro, Melinda; Yang, Jian; Han, Shikui; Lu, Qipeng; Zhang, Hua
Abstract: The incorporation of metal–organic frameworks (MOFs) into membrane‐shaped architectures is of great importance for practical applications. The currently synthesized MOF‐based membranes show many disadvantages, such as poor compatibility, low dispersity, and instability, which severely limit their utility. Herein, we present a general, facile, and robust approach for the synthesis of MOF‐based composite membranes through the in situ growth of MOF plates in the channels of anodized aluminum oxide (AAO) membranes. After being used as catalysis reactors, they exhibit high catalytic performance and stability in the Knoevenagel condensation reaction. The high catalytic performance might be attributed to the intrinsic structure of MOF‐based composite membranes, which can remove the products from the reaction zone quickly, and prevent the aggregation and loss of catalysts during reaction and recycling process.